Methanol extract of Muntingia calabura leaves attenuates CCl4-induced liver injury: possible synergistic action of flavonoids and volatile bioactive compounds on endogenous defence system - Zakaria, Zainul Amiruddin; Mahmood, Nur Diyana; Omar, Maizatul Hasyima; Taher, Muhammad; Basir, Rusliza (Taylor and Francis, 2019)
Context: Muntingia calabura L. (Muntingiaceae) exerts antioxidant and anti-inflammatory activities, thus, it might be a good hepatoprotective agent.